A concise synthesis of (±)-7-O-galloyltricetiflavan. Issue 26 (18th April 2018) - Zhang, Wenxuan; Xue, Wenjie; Jia, Yuqing; Wen, Gang; Lian, Xu; Shen, Jing; Liu, Ailin; Wu, Song
Abstract : We report the first total synthesis of (±)-7- O -galloyltricetiflavan (1a ) in five steps as well as an interesting discovery during the demethylation process. Abstract : (±)-7- O -galloyltricetiflavan (1a ) was synthesized successfully in five steps from the commercially available trihydroxyacetophenone (2 ) and trimethoxybenzoyl chloride (3 ). The flavone4a was prepared in a one-pot reaction and it gave hex- O -methylflavan6 followed by acylation and reduction. However, the demethylation of flavan6, 5- O -acetylflavan10 and 5- O -phenylacetylflavan11 by BBr3 gave all the hydrolyzed fragments7 and8 as the major products. By contrast, in the same condition, hept- O -methylflavan9 could provide the desired product (±)-7- O -galloyltricetiflavan (1a ) in 91% yield. The additional 5- O -B-Br2 complex may stabilize the ester bond during the demethylation process.